THE IMPACT OF LEADERSHIP STYLES ON ORGANIZATIONAL PERFORMANCE AND EMPLOYEE SATISFACTION: A CASE STUDY APPROACH - Gu Yu; Ooi Kok Loang; Guo Meiling; Wang Junzahng (International Journal of Accounting, Finance and Business, 2023)
Leadership style is significant for improving the organizational performance and satisfaction for the employees working within the organisation. The leadership styles include factors like motivation, effective communication, flexibility, and collaboration. The aim of the study is to analyse the impact of the leadership styles on the performance of the organisation and employee satisfaction. The researcher has made use of the Behavioural Theory in order to support the study on the effect of the leadership styles on the organizational performance (Loang & Ahmad, 2022). The researcher makes use of 50 employees of the financial sector of Malaysia in order to conduct the study. The researcher makes the use of primary data collection method and quantitative data analysis so that survey of the respondents can be conducted to obtain the results of the study. IBM SPSS statistics software is used for analysis in order to obtain the results of the study. The researcher observed that motivation and effective communication have a direct and significant impact on the performance of the employees. System effects the relationship between motivation and organizational performance.